Building Cost Comparison Between Conventional And Some Selected Industrialised Building Systems - Hj.Haron, Nuzul Azam (2002)
The Malaysian construction industry is undergoing a transitional change from an industry employing conventional technology to a more systematic and mechanised. This new system is now known as the industrialised building system (IBS). The new methods of construction can increase productivity and quality of work through the use of better construction machinery, equipment, materials and extensive pre-project planning. This study becomes very necessary since there is yet no organised body, which can provide the necessary information on the building cost comparison between the conventional and industrialised building system in Malaysia's construction industry.The thesis addresses the building cost comparison of the conventional system and industrialised building system of IBS A, IBS B, and IBS C. It provides the detail building cost to show cost savings amongst the conventional system and the IBS. The data were collected through questionnaire survey and case studies, which consisted of residential and institutional buildings. Through the t-test it is shown that there is a significant difference of cost saving for the conventional system as compared to the industrialised building system.